Metapsicologia della catacresi - Ognibene, Fabio (Metapsychologica - rivista di psicanalisi freudiana, 2023)
The rhetorical figure called catachresis has been defined from the need to designate an object or a concept devoid of a proper name. It would remedy to an inopia linguae; but what is the cause of this lack of language and how it originates? We have found a mechanism similar to that of Catachresis studying Freud’s theory of anaclisis, where in a similar way the sexual drives appropriate and «exploit» the Ego’s drives. We have divided two kinds of catachresis: those that use the terminology linked to the semantic and lexical field of the human body (incorporation); those based on the psychological mechanism of displacement. Furthermore, we have found a connection between the formation of automatic anxiety and the first type of catachresis, and between the signal anxiety and the second type. We have demonstrated how, in the clinical case of Hans, Freud formalized the Catachresis implied in the formation of the child’s symptoms and, revealing them by his interpretation, he laid the conditions for the resolution of the pathogenic conflict.